Changes in Working Model According to Transformed Work Conditions in the Pandemic - Gjorgjioska, Emilija; Sotiroski, David; Obednikovska, Snezana (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Abstract: Covid-19 pandemic is affecting our everyday life in all possible ways. It is also affecting companies and their employees. Things have changed over the past 24 months as many workers have developed a taste for a more flexible working model. Some are facing the benefits of working from home, but for some it is not such a positive experience. Human resources management should adjust to the new needs. Those needs are new forces that are driving transformational changes across companies, industries and economies issuing new strategic platforms in companies. Digitalization is promising a new era for working life according to new cultural transformation. All of this raises the need for the companies to change strategies and models in a way to adjust working conditions according to alteration of their employees in each way. While many executives would certainly prefer to return to the old model, it is more than clear that they all need to adjust their models to the new working platform. In this paper we would point out the benefits and risks of working from home. Also, we would analyze the legal frame in the Republic of North Macedonia, boundaries, and perspectives for modernization of Labor law. According to the results from the questionnaire that we will provide, we will suggest models for human resources transformation in the companies that will be more effective for the management and employees affected by this transformed pandemic situation.